Dynamics of Adsorptive Systems for Heat Transformation Optimization of Adsorber, Adsorbent and Cycle - Sapienza, Alessio (SpringerBriefs in Applied Sciences and Technology,, 2018)
This book investigates the adsorption dynamics of water, methanol, ethanol, and ammonia vapor on loose and consolidated adsorbent beds, as well as the impact of this aspect on the overall performance of adsorption systems for heat transformation. In particular, it presents the results of kinetic measurements made using the large temperature jump (LTJ) method, the most efficient way to study adsorption dynamics under realistic operating conditions for adsorptive heat transformers. The information provided is especially beneficial for all those working on the development of novel adsorbent materials and advanced adsorbers for heating and cooling applications. Today, technologies and systems based on adsorption heat transformation (AHT) processes offer a fascinating option for meeting the growing worldwide demand for air conditioning and space heating. Nevertheless, considerable efforts must still be made in order to enhance performance so as to effectively compete with commonly used electrical compression and absorption machines. For this purpose, intelligent design for adsorption units should above all focus on finding a convenient choice of adsorbent material by means of a comprehensive analysis that takes into account both thermodynamic and dynamic aspects. While the thermodynamic properties of the AHT cycle have been studied extensively, the dynamic optimization of AHT adsorbers is still an open issue. Several efforts have recently been made in order to analyze AHT dynamics, which greatly influence overall AHT performance. .